2002
DOI: 10.1088/0953-8984/15/2/306
|View full text |Cite
|
Sign up to set email alerts
|

Surface photovoltage spectroscopy as a valuable nondestructive characterization technique for GaAs/GaAlAs vertical-cavity surface-emitting laser structures

Abstract: We have investigated an 850 nm GaAs/GaAlAs (001) vertical-cavity surface-emitting laser (VCSEL) structure using angle- and temperature-dependent surface photovoltage spectroscopy (SPS). The SPS measurements were performed as functions of angle of incidence (0° ≤ θ ≤ 60°) and temperature (25° C ≤ T ≤ 215° C) for both the metal–insulator–semiconductor (MIS) and wavelength-modulated MIS configurations. Angle-dependent reflectance (R) measurements have also been performed to illustrate the superior features of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…However, there are still open questions in the analysis of the results obtained by the MIS technique. Usually, only the SPV amplitude spectrum is considered in the literature [10][11][12][13][14][15] and little attention is paid to the information that can be retrieved from the SPV phase spectrum. The SPV phase spectra have been discussed mainly in terms of relative changes 1 Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are still open questions in the analysis of the results obtained by the MIS technique. Usually, only the SPV amplitude spectrum is considered in the literature [10][11][12][13][14][15] and little attention is paid to the information that can be retrieved from the SPV phase spectrum. The SPV phase spectra have been discussed mainly in terms of relative changes 1 Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of nano-scale TiO 2 electrodes using the SPV technique, Wang et al [8] found that when modified with PbS, the surface states of TiO 2 are greatly suppressed; Jing et al [9] found that on the surface of a n-TiO 2 /Ti film, the amount of Ti 3+ surface states is low or non-existent and the SPV response is possibly related to the surface states resulting from the surface hydroxyl groups; Qian et al [10] reported that TiO 2 nanoparticles prepared from basic sols have more defects than those prepared from acidic sols and the incorporation of CdS can decrease the surface state density on TiO 2 electrodes. In this type of SPV technique, usually only the SPV amplitude spectrum has been considered in the literature [8][9][10][11][12][13][14][15], and little attention has been paid to the information in the SPV phase spectrum. In some reports [16,17], the SPV phase spectrum has been discussed, but just as a complement of the SPV amplitude spectrum.…”
Section: Introductionmentioning
confidence: 99%